(untitled) (International Journal of Studies in Nursing, 2023)
Background: The worldwide prevalence of hypertension people aged 25 and above is more than 40%. Data accuracy for blood pressure is important to diagnosis and treatment. In self-complaints among patients in cardiology outpatient clinic, the incidence of incorrect blood pressure measuring was 11.9%. Aims: Enhanced accuracy for blood pressure measurement in the outpatient setting. Method: Clinical audits were conducted using the JBI Practical Application of Clinical Evidence System (JBI PACES). With the 7 audit criteria recommended by best practice, improvement and audits were performed for 22 weeks for evaluation of improved quality for blood pressure measurement. Result: Standard documentation complying with recommended clinical guidance was established, with the organized educational training program and environmental renovation, the project’s performance in improvement was significantly enhanced, compliance with clinical practice guidelines before implementation of 35%-90% increased achieving 70%-100% after implementation. Noise in the outpatient setting of 62 dB decreased to 52 dB, with daily incidence of 11.9% for complaint in incorrect blood pressure measuring decreased to 1.1%. Conclusion: Evidence-based practice project successfully enhanced the accuracy for blood pressure measurement in outpatients. Recommendation: The empirical application of quality improvement in blood pressure measurement accuracy achieves progressive results. The important factors are the completion of environmental transformation, the establishment of standard documents, the education of patients and health care volunteers, and the maintenance of the effect through continuous review.